A rare presentation of Tolosa – Hunt syndrome in a young male (Indian Journal of Case Reports, 2026)
The primary care provider, nurse practitioner, and internist often encounter patients with a headache. However, when they encounter a patient with an intense headache and ophthalmoplegia, the care plan no longer resides with a general practitioner, and referral to a neurologist becomes mandatory. This is due to the vast differentials involved and rare pathologies that one may come across during their medical practice. One such case of a 45-year-old male with similar complaints encountered during a routine emergency day led to a diagnosis of a rare neuro-immunological disorder, possibly a diagnosis of exclusion.